Menyusun Strategi Pembelajaran Bipa Yang Efektif Untuk Penutur Asing Tingkat Pemula - Monika Aprilia; Romauli Angelika; Safinatul Hasanah Harahap; Yesi Jesika Sitepu (Departement of Mathematics Education, 2024)
BIPA's strategy in planning teaching must involve the use of 3D animated films and e-book media because these two tools are very important to achieve learning objectives. The preparation of strategies and materials needs to be done carefully so that learning is effective. This research uses the library study method, which is a research approach carried out by examining books, literature, notes, reports and literary works that are relevant to the problem being researched. The goal is so that students can easily understand the material taught by the teacher. One way to achieve this is by elaborating on strategies and material related to elections, as well as adding local elements so that the material is not too difficult for students to understand. Therefore, strategic management and organization are essential to ensure learning is structured in the most effective and efficient way to achieve the desired goals